Consumer Protection of Girls from Cybercrime in a Gender Perspective - Suparto, Susilowati; Yuanitasari, Deviana; Judiasih, Sonny Dewi; Salaeh, Yamudin (Journal of Law and Legal Reform, 2024)
Cybercrime covers a wide range of illegal acts carried out through the Internet or other digital devices, including fraud, identity theft, hacking, the spread of malware, to sexual exploitation of children. Girls are often the primary targets of these various forms of cybercrime. This is due to several factors, such as higher emotional vulnerability, still strong gender stereotypes, as well as a lack of education and awareness about cybersecurity among girls. Therefore, special protection that takes into account a gender perspective is essential to reduce the risk and impact of cybercrime against girls. In addition to the above cases, there are many more cases of cybercrime against girls in Indonesia that have not been or received public attention. Cybercrime is a serious threat that needs to be addressed seriously and urgently. So it is necessary to study further the impact of cybercrime on girls and to analyze gender perspectives in protecting girls' consumers as vulnerable consumers. Education on cybersecurity should start early, with a special focus on girls. Strict regulations and policies are needed to protect girls from sexual exploitation and other cybercrimes. Using protective technologies such as antivirus software and parental monitoring apps can help reduce the risk of girls becoming victims of cybercrime. Psychological and social support is crucial in helping girls who are victims to cope with the negative impact of cybercrime. Collaboration between various institutions and communities is essential to creating a secure and supportive digital environment for girls.